2015
DOI: 10.1016/j.jcrs.2014.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Mydriatic insert and intracameral injections compared with mydriatic eyedrops in cataract surgery: Controlled studies

Abstract: Dr. Behndig has received fees from Théa Pharma GmbH as a member of the European Team for the Prophylaxis of Infection in Cataract Surgery group. Dr. Korobelnik has received consultancy fees from Alcon Surgical, Inc.; Allergan, Inc.; Alimera, Inc.; Bayer HealthCare AG; Carl Zeiss Meditec AG; Novartis Corp.; Roche Innovatis AG; and Théa Pharma GmbH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 116 publications
(234 reference statements)
0
41
0
Order By: Relevance
“…Topical mydriatic eyedrops are currently the standard method for routine pupil dilation in cats that must undergo corneal and intraocular surgeries . The main disadvantages of mydriatic eyedrops are related to delayed local effect . The delayed onset of dilation is due to the slow penetration of active ingredients through the cornea, and the time to effective dilation is longer than the cataract surgery procedure itself .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Topical mydriatic eyedrops are currently the standard method for routine pupil dilation in cats that must undergo corneal and intraocular surgeries . The main disadvantages of mydriatic eyedrops are related to delayed local effect . The delayed onset of dilation is due to the slow penetration of active ingredients through the cornea, and the time to effective dilation is longer than the cataract surgery procedure itself .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it has been shown that the intracameral administration of 0.001% epinephrine induce fast, satisfactory, and long‐lasting mydriasis to perform phacoemulsification and intraocular lens implantation . In humans, several studies have reported that the intracameral injection of 1%‐2% lidocaine provides safe and effective pupil dilation for cataract surgery . In dogs, the time to onset of mydriasis is related to both the concentration and volume of lidocaine administered in the anterior chamber .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6) Therefore, intraocular irrigation with 1 µg/mL adrenaline is widely used to maintain pupil dilation during surgery. [6][7][8] The irrigating solution kit consists of oxidized glutathione and its dilute solution at physiological pH and osmolality. Because the solution does not contain an antioxidant such as sodium bisulfite, the dissolved adrenaline is unstable.…”
mentioning
confidence: 99%